2021
DOI: 10.1037/dev0001209
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal relations of subjective sleep quality and affective well-being in late childhood.

Abstract: High sleep quality has been associated with beneficial outcomes across the lifespan. Intensive longitudinal studies suggest that these beneficial effects can also be observed on a day-to-day level. However, the dynamic interplay between subjective sleep quality and affective wellbeing in children's daily life has only rarely been investigated. The aims of the present work were (a) to replicate findings from a prior ambulatory assessment study in this area (Könen et al., 2016), (b) to explore the effect of subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…We also inspected the trace and autoregressive plots to ensure the credibility of the results. As suggested by previous studies using Bayesian estimators (Neubauer et al, 2021; Sokolovic et al, 2021), we reported the median of the posterior parameter distribution and associated 95% credible intervals (CIs). If the parameters’ 95% CI did not contain zero, we then reported the results as statistically significant (Neubauer et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We also inspected the trace and autoregressive plots to ensure the credibility of the results. As suggested by previous studies using Bayesian estimators (Neubauer et al, 2021; Sokolovic et al, 2021), we reported the median of the posterior parameter distribution and associated 95% credible intervals (CIs). If the parameters’ 95% CI did not contain zero, we then reported the results as statistically significant (Neubauer et al, 2021).…”
Section: Methodsmentioning
confidence: 99%